Análisis químico y determinación de la actividad antioxidante de la fracción volátil destilada desde la especie orégano (Origanum vulgare) - Robles Robles, Andrea Lisseth (2018)
Abstract:The essential oil of the species Origanum vulgare, is isolated through steam distillation. The chemical composition of the essential oil was determined by gas chromatography coupled to GC/MS mass spectrometry and the CG/FID flame ionization detector. The biological activity was evaluated by microdilution method in broth and the antioxidant activity by two spectrophotometric methods: ABTS and DPPH. In addition, the physical properties of the essential oil were determined. Thirty compounds were identified that correspond to 98.58% of the total composition of the essential oil, the most representative compounds were: γ-Terpinene (22.75%), Linalool (21,05%), Terpinen-4-ol (9,50%), (Z) -β Ocimene (6.36%) and o-Cymene (6.06%). The oil density was 0.9250 g/cm3, the refractive index was 1.4792 and the optical activity was +14.4 °. The essential oil showed remarkable activity against Staphylococcus aureus ATCC 25923. Essential oil present antioxidant activity for both evaluated methods.